2016
DOI: 10.1007/s12105-016-0685-x
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 (Cx43) Expression in Laryngeal Squamous Cell Carcinomas: Preliminary Data on Its Possible Prognostic Role

Abstract: The aim of the report is to evaluate the prognostic and predictive role of Connexin 43 (Cx43) expression in laryngeal squamous cell carcinomas. Eighty-seven previously untreated patients submitted to laryngectomy ± neck dissection ± radiotherapy were enrolled in this retrospective study. The original primary tumor slides were reassessed, tumor grade and stage reviewed, and Cx43 immunohistochemical analysis performed: only cytoplasmic membranous staining of Cx43 has been shown. Neither significant correlation h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
1
6
0
2
Order By: Relevance
“…In our previous study, we found that Cx43 could be regarded as a prognostic factor in head and neck cancers, and the reduction of its expression level is associated with a significantly poorer prognosis [14]. This was confirmed by Puzzo et al in laryngeal cancers [24]. However, other studies found inverse association between Cx43 expression and overall survival suggesting, that Cx43 has different role in certain tumor types (esophageal, oropharyngeal) or localization (cytoplasm and nucleus vs. membrane) [25][26][27].…”
Section: Discussionsupporting
confidence: 61%
“…In our previous study, we found that Cx43 could be regarded as a prognostic factor in head and neck cancers, and the reduction of its expression level is associated with a significantly poorer prognosis [14]. This was confirmed by Puzzo et al in laryngeal cancers [24]. However, other studies found inverse association between Cx43 expression and overall survival suggesting, that Cx43 has different role in certain tumor types (esophageal, oropharyngeal) or localization (cytoplasm and nucleus vs. membrane) [25][26][27].…”
Section: Discussionsupporting
confidence: 61%
“…In certain tumors where Cx43 is detected at the cell surface, the levels of Cx43 were reversely correlated with lymph node metastasis and prognosis [38, 39] (Table 1). The above studies suggested the inhibitory roles of Cx43 in tumorigenesis.…”
Section: Connexin 43mentioning
confidence: 99%
“…25 In another study in the same direction, Bertram 26 reported that increasing Cx43 expression reduced normal and neoplastic tissue proliferation, decreased dysplastic tissue, and reduced tumor progression. In a study by Puzzo et al, 27 they reported that the expression of connexin Cx43 in poorly differentiated carcinoma was negative or poorly stained. In the study performed by Wilgenbus et al, 28 benign tumors, and some malign tumors were studied.…”
Section: Discussionmentioning
confidence: 97%